VET Data Report Germany 2015 : facts and analyses accompanying the Federal report on vocational education and training - selected findings - Le Mouillour, Isabelle [Herausgeber]; Friedrich, Michael [Herausgeber] (Bundesinstitut für Berufsbildung, 2016)
"The development of the German vocational education and training system and more specifically of the dual system relies on regular data collection. Statistical analysis and surveys are continuously informing policy decisions and supporting practices. Traditional aspects of apprenticeship in terms of indicators on apprentices, companies or occupations are provided. Each year BIBB colleagues select a key topic by relevance to VET stakeholders in Germany: The 2015 report delivers in-depth data on matching relationship between training system and labour market needs and oversights on future shortages of skilled workers in Germany. The Data Report of the Federal Institute for Vocational Education and Training (BIBB) is a selection of most relevant and actual data on the German Vocational Education and Training system. Full data is provided in German language on BIBB website (www.bibb.de/datenreport)." (Editor, BIBB-Doku)
Keywords: G 1.3 Aus- und Weiterbildungsmarkt; G 1.2.3.2 Anforderungen & Bedarfe; S 2.3 Berufsbildungspolitik; S 1.5.2 Berufliche Weiterbildung; S 1.3.1 Ausbildung im Dualen System; Berufsbildungsbericht; Berufsbildungsstatistik; Berufsbildungspolitik; Berufsausbildung; Ausbildungsstellenmarkt; Fachkräftebedarf; Mismatch; Mobilität